Molecular responses to strength and endurance training: Are they incompatible? - Hawley, J. A. (Applied Physiology, Nutrition, and Metabolism, 2009)
Simultaneously training for both strength and endurance results in a compromised adaptation, compared with training for either exercise mode alone. This has been variously described as the concurrent training effect or the interference effect. It now appears that the genetic and molecular mechanisms of adaptation induced by resistance- and endurance-based training are distinct, with each mode of exercise activating and (or) repressing specific subsets of genes and cellular signalling pathways. This brief review will summarize our current understanding of the molecular responses to strength and endurance training, and will examine the molecular evidence for an interference effect when concurrent training is undertaken. A better understanding of the activation and interaction of the molecular pathways in response to these different modes of exercise will permit sport scientists to develop improved training programs capable of maximizing both strength and endurance.